Motives behind students’ academic achievement and participation in sports activities: A case study of adolescents in Benin Republic secondary schools - EDOH, KOFFI PIERROT (My University, 2012)
Francophone students from North Africa attach more importance to academic studies than their European counterparts who are more attracted to sports and arts. To our knowledge, the attitude of learners from black African countries has not been studied. The objective of this study was to assess how students perform in Benin secondary schools when they are involved in academic pursuits and or in school sports competitions (SSC). For this purpose, two questionnaires were administered: the first one has to do with the school academic work and was addressed to 271 students who do not participate in SSC (non-sports students); the second one related to SSC was administered to 138 students enrolled in school athletic federations (student-athletes). The 271 non-sports students appeared more persistent within academic work in which they are willing to repeat in case of failure, while the 138 student-athletes tended to withdraw from the SSC in case of difficulties (their rate of amotivation, 0.13 and 0.21 respectively are significantly different). This difference shows that the students have different types of motivation in academic work and sports activities. The school implements a curriculum which is designed according to the State policy regarding training and education. It prepares for degrees which offer employment opportunities. In these conditions, students give more importance to school programmes than to sport. Indeed, they think that sport merely helps them to improve their performance in the sports disciplines they through physical education (PE) and satisfy at the same time their need for entertainment
Keywords: Motivation; Students'Behaviour; School; sport